Library Technology Materials A Bibliography - Woods, William E.; Chicago City Colleges, IL. Kennedy-King Coll. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This bibliography of 184 items was compiled in connection with the Library Technology Program of the Kennedy-King College. The items listed were acquired by the college library to support the course work. Pamphlets, books and periodical titles are included, and items suggested for initial purpose are indicated. (JB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Instructional Materials; Library Education; Library Technicians